Evaluating the influence of noise emitted by environmental enrichment equipment in routine farrowing management practices - Ricci, Gisele Dela; Sousa, Rafael Teixeira de; Miranda, Késia Oliveira da Silva; Tonon, Elder; Passere, Ana Laura Alves de Matos; Titto, Cristiane Gonçalves (Revista de Ciências Agroveterinárias, 2020)
The installation of fans and rooftop sprinklers in swine housing and management facilities can increase noise intensity and may impair workers' hearing health over longs periods of time; therefore, an assessment of the piglets’ stress during invasive practices was made. This study set out to evaluate the noise intensity emitted by environmental enrichment devices (fans and rooftop sprinklers) and by piglets restrained for body temperature assessments and its effect on animal welfare and on the hearing health of workers exposed to it for long periods. Twenty piglets ranging in age from five to twenty days were observed. The sow gestation area was divided into a cooled (fans and rooftop sprinklers) and uncooled area. Two decibel meters were used to measure noise intensity, one for the general noise in the facilities and the other for the piglets, with five-minute intervals between assessments. Digital thermometers were used to take the rectal temperature, and infrared thermometers were used to take the body surface temperature. Fixed-effects ANOVA for the housing environment and periods and multiple comparisons at a significance level of 5% were applied. The average dorsal temperature of the piglets was 36 °C ± 1.2 in the cooled area and 38.4 °C ± 0.5 in the uncooled area. In both periods, the average maximum noise intensity was over 100 decibels. In the afternoon, the maximum intensity was higher for the uncooled environment. The results indicate that neither the fans nor the rooftop sprinklers installed in the facilities nor the squealing piglets during restraint affect the noise intensity of the environment. However, the noise intensity demonstrates the piglets’ stress and the need for protective equipment to preserve the workers’ hearing health.